Kajian Potensi Tumbuhan Nipah (Nypa fruticans Wurmb.) di Desa Tabanio Kabupaten Tanah Laut - Jumidah Jumidah; Anang Kadarsah; Sasi Gendro Sari (Jurnal Natural Scientiae, 2021)
Nipah or Nypa fruticans (Thunb.) Wurmb is a member of the palmae tribe that lives along the river coast grouped in a mangrove forest ecosystem that is influenced by tides. Currently Nipah is used as a source of livelihood for the people of Tabanio Village, Tanah Laut Regency. This study aims to find out information about the potential of stands, the parts of the plant that are used and to study the potential of Nipah plants. This type of research is observative on the Nipah plant. The method used to explore the various potentials of Nipah leaves is done by taking an inventory of the presence of nipah plant stands using the plot sampling method with the compartmental path technique. Furthermore, measurements of plant parts were carried out according to the criteria used, in each plot 3 plant samples were taken. Meanwhile, to explain the use of Nipah leaves by the people of Tabanio Village, data was collected using interviews through questionnaires. Based on the results of this study, the total density of nipah plants was 1,231.3 ind / ha with a plant height of 10.4 m.